FEATURES EPIZOOTOLOGY ANOPLOCEPHALIDOZIS HORSES IN THE CRIMEA - Лук’янова, Г. О. (Scientific Progress & Innovations, 2014)
Studied seasonally and age invasia anoplocephalidosis of horses in different climatic and landscape zones Crimea. Maximum infestation of anoplocephalata in horses registered in the foothill and mountain areas. The steppe zone is present bot generally not observed. The most common pathogens detected species Anoplocephala perfoliata (in 63 of 71 affected horses of anoplocephalata – 87,3%). The most invazia observed in the autumn. Young animals 1 to 3 years of age had the highest rates of infestation cestodes intestin (EI – 26,3%). Adult horses were infested by only 5,7%.